2011
DOI: 10.1186/1471-2407-11-133
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell cancer among African Americans: an epidemiologic review

Abstract: Incidence rates for renal cell cancer, which accounts for 85% of kidney cancers, have been rising more rapidly among blacks than whites, almost entirely accounted for by an excess of localized disease. This excess dates back to the 1970s, despite less access among blacks to imaging procedures in the past. In contrast, mortality rates for this cancer have been virtually identical among blacks and whites since the early 1990s, despite the fact that nephrectomy rates, regardless of stage, are lower among blacks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 112 publications
1
43
0
Order By: Relevance
“…While previous reports suggest that factors including a higher prevalence of hypertension, smoking, alcohol use and lack of access to care underlie this survival disparity [3, 4, 6, 8], this survival disparity may also be explained by the present study's identification of distinct tumor biology between black and white patients with papillary RCC [9]. Specifically in the present study's supervised whole genome expression analysis between 58 black and 58 white propensity score matched patients with pRCC, we identified a distinct tumor biology as demonstrated by enrichment of immune related pathways including the B cell receptor signaling pathway, NOD-like receptor signaling pathway, and genes involved in defensins, VEGF and more specifically overexpression of CRYBB2 associated with the WNT signaling pathway in black patients.…”
Section: Discussionmentioning
confidence: 99%
“…While previous reports suggest that factors including a higher prevalence of hypertension, smoking, alcohol use and lack of access to care underlie this survival disparity [3, 4, 6, 8], this survival disparity may also be explained by the present study's identification of distinct tumor biology between black and white patients with papillary RCC [9]. Specifically in the present study's supervised whole genome expression analysis between 58 black and 58 white propensity score matched patients with pRCC, we identified a distinct tumor biology as demonstrated by enrichment of immune related pathways including the B cell receptor signaling pathway, NOD-like receptor signaling pathway, and genes involved in defensins, VEGF and more specifically overexpression of CRYBB2 associated with the WNT signaling pathway in black patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous epidemiologic studies suggest that no particular type of commonly used antihypertensive medications was consistently associated with RCC risk, and that it is hypertension itself that plays a role in the etiology of this malignancy. [1, 4, 13, 15, 16, 31] Fourth, Shanghai is one of the most industrialized cities in China, and our study was based on two cohorts conducted in urban Shanghai. Thus, the results may not be generalized to the whole population of China, especially rural China.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies, primarily conducted in Western populations, have consistently shown that hypertension and obesity are among the strongest risk factors for renal cell carcinoma (RCC). [15]…”
Section: Introductionmentioning
confidence: 99%
“…Globally, they are more common in developed rather than developing countries and in males rather than females 2 . About 85% of all kidney cancers arise from the renal parenchyma (termed as renal cell carcinomas or RCCs) while the remaining arise from the urothelium lining the renal pelvis 3 . It is estimated that nearly 58,240 cancers of the kidney and renal pelvis were diagnosed in the United States in 2010, and about 13,040 patients died from these malignancies in the same period.…”
Section: Introductionmentioning
confidence: 99%